2021
DOI: 10.1021/acsinfecdis.1c00055
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies of Acetazolamide-Based Carbonic Anhydrase Inhibitors with Activity against Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae is an urgent threat to public health in the United States and around the world. Many of the current classes of antibiotics to treat N. gonorrhoeae infection are quickly becoming obsolete due to increased rates of resistance. Thus, there is a critical need for alternative antimicrobial targets and new chemical entities. Our team has repurposed the FDA-approved carbonic anhydrase inhibitor scaffold of acetazolamide to target N. gonorrhoeae and the bacteria's essential carbonic anhydrase, Ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 80 publications
1
44
0
Order By: Relevance
“…Thus, there is an urgent need for new classes of antibiotics which can either inhibit the growth of these pathogens and subsequently kill them, or of compounds which can restore the sensitivity of resistant bacteria to the various classes of clinically used agents 3–5 . The inhibitors of the widespread metalloenzyme, carbonic anhydrase (CA, EC 4.2.1.1), were recently shown to be effective in inhibiting the growth (possessing a significant bactericidal activity) of some drug-resistant pathogens, such as vancomycin-resistant Enterococci 5 and Neisseria gonorrhoeae 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is an urgent need for new classes of antibiotics which can either inhibit the growth of these pathogens and subsequently kill them, or of compounds which can restore the sensitivity of resistant bacteria to the various classes of clinically used agents 3–5 . The inhibitors of the widespread metalloenzyme, carbonic anhydrase (CA, EC 4.2.1.1), were recently shown to be effective in inhibiting the growth (possessing a significant bactericidal activity) of some drug-resistant pathogens, such as vancomycin-resistant Enterococci 5 and Neisseria gonorrhoeae 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the scientific community was rather sceptical for a long time that bacterial CA inhibition may lead to significant growth inhibition of pathogenic bacteria, Flaherty’s group recently published the long-awaited 5 , 6 proof-of-concept that inhibition of bacterial CAs may lead to antibiotics with novel mechanisms of action. They showed that the sulphonamide CA inhibitor (CAI) acetazolamide and some of its derivatives, as well as dorzolamide, outperformed the current drug of choice, linezolid, both in vitro and in vivo , for inhibiting the growth of vancomycin-resistant enterococci (VRE) 5 and N. gonorrhoeae 6 . Furthermore, other groups have demonstrated that CAIs may exhibit reduced potential for the development of drug resistance, as in the case of H. pylori and ethoxzolamide as CAI.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, considering the scarcity of NgCA inhibition data, for which only 4 anions were investigated using the esterase activity 23 , as mentioned earlier, together with the extensive sulphonamide inhibition study reported recently by us 15 , we investigated here the inhibition profile of this enzyme with a large series of inorganic metal-complexing, simple and complex anions, as well as small molecules known to act as CAIs 12 , 16 , such as sulfamide, sulphamic acid, phenylboronic acid, phenylarsonic acid and N,N -diethyl-dithiocarbamate ( Table 1 ). The stopped-flow, CO 2 hydrase assay was used to measure the inhibition constants shown in Table 1 , and the same data for the inhibition of the red blood cell human isoforms hCA I and II 12 , 16 were also included for comparison reasons.…”
Section: Resultsmentioning
confidence: 99%
“…NgCA was a recombinant enzyme obtained in-house as described earlier 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation